Molecular and Antigenic Properties of Mammalian Cell-Expressed Theileria parva Antigen Tp9 - Bastos, Reginaldo G.; Franceschi, Valentina; Tebaldi, Giulia; Connelley, Timothy; Morrison, W. Ivan; Knowles, Donald P.; Donofrio, Gaetano; Fry, Lindsay M. (Frontiers in Immunology, 2019)
East Coast Fever (ECF), caused by the tick-borne apicomplexan parasite Theileria parva, is a leading cause of morbidity and mortality in cattle of sub-Saharan Africa. The infection and treatment method (ITM) is currently the only vaccine available to control T. parva. Although ITM elicits levels of protection, its widespread adoption is limited by costs, laborious production process, and antibiotic co-treatment requirement, necessitating the development of a more sustainable vaccine. To this end, efforts have been concentrated in the identification of new T. parva vaccine antigens and in the development of suitable platforms for antigen expression. In this study we investigated the molecular and antigenic properties of T. parva antigen Tp9 expressed by mammalian cells. Data indicate that Tp9 contains a secretion signal peptide that is weakly functional in mammalian cells. Thus, Tp9 secretion from mammalian cells increased ten-fold after the native signal peptide was replaced with the human tissue plasminogen activator secretion signal peptide (tPA). Sera from all T. parva–immune cattle recognized this recombinant, secreted Tp9. Additionally, PBMC from ITM-immunized cattle produced significant (p < 0.05) amounts of IFNγ following ex vivo exposure to Tp9, but this response varied between cattle of different MHC class I and class II genotypes. In addition, depletion experiments demonstrated that IFNγ to Tp9 was primarily produced by CD4+ T cells. Molecular analysis demonstrated that Tp9 presents a secretion signal peptide that is weakly functional in mammalian cells, suggesting that it remains within lymphocytes during infection. Tp9 secretion from mammalian cells was substantially increased when the tPA secretion signal sequence was substituted for the native secretion signal sequence. Using full-length, recombinant Tp9 secreted from mammalian cells, we demonstrated that T. parva–immune cattle develop both humoral and cellular immune responses to this antigen. Collectively, these results provide rationale for further evaluation of Tp9 as a component of a T. parva subunit vaccine.